Cultural norms and cultural agents in buyer–seller negotiation processes and outcomes. Issue 2 (2nd April 2016) - Uzo, Uchenna; Adigwe, Jude O.
Abstract : Although a good number of studies have significantly investigated the role of culture in buyer–seller negotiation processes and outcomes, fewer studies have investigated the role of individual negotiators and organizations in shaping the cultural norms that affect negotiation processes and outcomes. Through a multi-case study of buyer–seller negotiations in five organizations that are illustrative of the informal economy of Nigeria, the study unpacks the role of individuals and organizations in shaping the cultural norms that affect the scope and outcomes of negotiation in an emerging market economy. We find that buyers and sellers play the role of inhabiting cultural norms which in turn narrow the scope of the negotiation to price considerations. On the other hand, the templates used by organizations to execute selling activities either maintain or deter the cultural norms that influence negotiation outcomes. Insights from the study extend the literatures on institutional work, culture and negotiation, sales negotiation in emerging markets.